A novel role for the pineal gland: Regulating seasonal shifts in the gut microbiota of Siberian hamsters. Issue 4 (2nd October 2020) - Shor, Elyan K.; Brown, Shawn P.; Freeman, David A.
Abstract: The gut microbiota plays a significant role in a variety of host behavioral and physiological processes. The mechanisms by which the gut microbiota and the host communicate are not fully resolved but include both humoral and direct neural signals. The composition of the microbiota is affected by internal (host) factors and external (environmental) factors. One such signal is photoperiod, which is represented endogenously by nocturnal pineal melatonin (MEL) secretion. Removal of the MEL signal via pinealectomy abolishes many seasonal responses to photoperiod. In Siberian hamsters ( Phodopus sungorus ), MEL drives robust seasonal shifts in physiology and behavior, such as immunity, stress, body mass, and aggression. While the profile of the gut microbiota also changes by season, it is unclear whether these changes are driven by pineal signals. We hypothesized that the pineal gland mediates seasonal alterations in the composition of the gut microbiota. To test this, we placed pinealectomized and intact hamsters into long or short photoperiods for 8 weeks, collected weekly fecal samples, and measured weekly food intake, testis volume, and body mass. We determined microbiota composition using 16S rRNA sequencing (Illumina MiSeq). We found significant effects of treatment and time on the abundances of numerous bacterial genera. We also found significant associations between individual OTU abundances and body mass, testis mass, and food intake, respectively. Finally, results indicate a relationship between overall community structure, and body and testis masses. These results firmly establish a role for the pineal gland in mediating seasonal alterations in the gut microbiota. Further, these results identify a novel neuroendocrine pathway by which a host regulates seasonal shifts in gut community composition, and indicates a relationship between seasonal changes in the gut microbiota and seasonal physiological adjustments.